So you want to solve
Integral ( x(2x - 1)^(1/2) ) dx
You're going to solve this using substitution, in a slightly different way.
Let u = 2x - 1. At this point, rather than solving for du directly, you're going to first solve for x, and then solve for dx.
u + 1 = 2x
(1/2) (u + 1) = x
Differentiating both sides,
(1/2)du = dx
Now, we make the appropriate substitution, Remember we want to substitute the x, the (2x - 1), and the dx, and we have all these values.
Integral ( x(2x - 1)^(1/2) ) dx becomes
Integral ( [(1/2)(u + 1)] [u^(1/2)] [(1/2)du] )
Let's pull out ALL constants from the integral. This is a step that makes integration easier, and it's a perfectly valid step too. Our constants in this case are (1/2) and another (1/2), so pulled out together, they become 1/4, and the integral becomes
(1/4) * Integral ( (u + 1) u^(1/2) du)
Note that we can now distribute the u^(1/2). Note that u * u^(1/2) is u^(3/2), so we have
(1/4) * Integral (u^(3/2) + u^(1/2)) du
Now, we integrate normally, using the reverse power rule.
(1/4) * [ (2/5)u^(5/2) + (2/3)u^(3/2) ] + C
Let's clean this up by multiplying the fractions out.
(1/10)u^(5/2) + (1/6)u^(3/2) + C
And now, we substitute in u = (2x - 1) back, to get
(1/10)(2x - 1)^(5/2) + (1/6)(2x - 1)^(3/2) + C
2007-01-15 12:46:29
·
answer #1
·
answered by Puggy 7
·
2⤊
0⤋
So Y=â«x*sqrt(2x-1)*dx,
assume z= sqrt(2x-1) or zz= 2x-1 or x=0.5(zz+1) and dx = zdz;
Y=â«(0.5(zz+1)) *z*(zdz) =
= 0.5â«(zzzz +zz)dz = 0.5((1/5)z^5 +(1/3)z^3) =
= (1/30)(3zz +5)zzz =
= (1/30)(3(2x-1) +5)* (2x-1)^(3/2) =
=(1/15) (3x+1) (2x-1)^(3/2) +C;
puggy's right!
2007-01-15 23:11:55
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋